Smart phone usage parental monitoring & control - Lau, Wei Qing (2022)

(untitled)
This project is a parental monitoring application for parent monitor children purpose .Therefore our target user is for the parent , the expected outcome of this project is to let the parent can have a tools or way more easier to monitoring and control their children by using the features functionality of this application such as screen time management , call log history and others . The methodology that has applied in this project is Agile Development Methodology because it is more suitable to mobile application development and it can have a further communication with client during the middle of progress. Therefore , we can have the correction or improvement immediately after receiving the feedback of client . Besides , the development tools that will be use in this project is the Android Studio for the coding purpose using the Java language . Firebase will be the tools of online database of this project and all the data will be store in Firebase . Adobe XD will be use to design the user interface (UI) design and it not involving the coding part.